Pengembangan Media e-Learning Mata Pelajaran Teknologi Informasi dan Komunikasi untuk Kelas XI SMA - Syahmaidi, Eril (LLDIKTI Wilayah X, 2015)
Penelitian ini bertujuan untuk menghasilkan media pembelajaran berupa media e-learning Berbasis Video yang valid untuk pelajaran Teknologi Informasi dan Komunikasi. Jenis penelitian ini adalah penelitian pengembangan dengan menggunakan model IDI (Instructional Development Institute). Untuk melihat apakah Media E-Learning Berbasis Video ini valid, dilakukan uji pakar. Desain ini divalidasi oleh 2 orang pakar, pakar perancangan Media E-learning Berbasis Video dan pakar Media E-Learning Berbasis Video. Hasil penelitian menunjukkan bahwa Media E-learning Berbasis Video pada aspek Akses E-Learning (93%), Aspek materi sangat valid (93%), aspek penyajian sangat valid (93%), aspek Media E-learning Berbasis Video sangatÂ valid (93%) serta aspek video Media E-learning sudah sangat valid (94%). Berdasarkan data di atas dapat disimpulkan bahwa Media E-learning Berbasis Video telah valid. Kata kunci: media; e-learning; video; teknologi informasiThis research is aimed to produce E-learning media based on valid, practical, and effective video for Communication and information technology subject. The background of the research is based on the writer observation in SMA N 2 Sungai Penuh. Media development is aimed to help the students to understand the topic about internet by providing online videos which can be accessed anywhere and anytime. This research is a research development which used IDI (Instructional Development Institute) model. To prove the validity, practicability, and the effectiveness of this Video-based E-learning media, the writer conducts expert test, one to one evaluation, small group evaluation, and filed test by observing the learning process and learning result of the student. This design is validated by two experts; Video-based E-learning media design expert and Video-based E-learning media development expert. The Video-based E-learning media is tested to 31 students of XI class semester 1 at SMA N 2 Sungai Penuh to figure out the practicability, and the effectiveness of this media. The result of this research shows that Video-based E-learning media in term of E-learning access is (93%). Material aspect is valid (93%), performance aspect is valid (93%), Video-based E-learning media aspect is valid (93%), and video aspect of media E-learning is valid (94%). The level of practicability, by the teacher is valid (96%) and by the student is valid as well (94%). Based on the above data it can be concluded that the Media E -learning Based Video was valid.Keywords: Media; e-learning; video; information technology